Feeling good and doing more: How does the customer respond to pro-customer deviance in the context of hospitality - Ji, Yiyu; Xu, Xiaoyan; Ji, Jingshu (Frontiers in Psychology, 2022)
Guided by the service-dominant logic, hospitality employees have to occasionally engage in pro-customer deviance to offer customized service. Whereas pro-customer deviance has been linked with several customer altitudinal outcomes, the different customers’ emotional and behavioral responses have not yet been clarified. This study explores customers’ responses towards customer-contact employee and enterprise respectively. In addition, to investigate the emotional and cognitive mechanisms underlying those response processes, this study introduces gratitude towards employee and customer-company identification as mediators in the relationship between pro-customer deviance and a series of customer extra-role behaviors. A multi-source field study was conducted to test a two-stage structural equation model. Results show that pro-customer deviance is positively related to customers’ positive feedback and service friendship towards employee via gratitude. Also, the customer-company identification is found to play a mediation role between pro-customer deviance and customers’ advocacy and prohibitive voice towards organization. Theoretical and managerial contributions are also discussed at the end.